CULTURAL COMMUNICATION IN THE DIGITAL ERA: : (Challenges, Strategies, And Social Implications) - Gautama, Sidartha Adi; Trenggono, Nanang; Kartika, Tina; Firman Ashaf , Abdul (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2025)
This study discusses the transformation of cultural communication in the digital age, which is characterised by rapid developments in information technology, social media, and globalisation. Using qualitative methods and literature review, this study identifies fundamental changes in the form, process, and impact of cultural communication on society. The findings reveal that the digital age has erased geographical boundaries, accelerated cultural exchange, and expanded social networks. However, challenges such as miscommunication, cultural polarisation caused by social media algorithms, and the spread of misinformation and hate speech have also increased. Proposed strategies include enhancing digital and cultural literacy, multicultural education, cross-sector collaboration, and innovation in cultural preservation through digitalisation. The social implications identified include strengthened social solidarity, the formation of hybrid identities, cultural economic opportunities, and the risk of identity crises and social conflicts. This study recommends collective cross-sector efforts to build a healthy, adaptive, and inclusive cultural communication ecosystem in the digital age.